Synthesis of Peptoids Containing Multiple Nhtrp and Ntrp Residues: A Comparative Study of Resin, Cleavage Conditions and Submonomer Protection - Lone, Abdullah; Arnous, Anis; Hansen, Paul Robert; Mojsoska, Biljana; Jenssen, Håvard (Frontiers in Chemistry, 2020)
Peptoids hold status as peptide-mimetics with versatile biological applications due to their proteolytic stability and structural diversity. Among those that have been studied in different biological systems, are peptoids with dominant balanced hydrophobic and charge distribution along the backbone. Tryptophan is an important amino acid found in many biologically active peptides. Tryptophan-like side chains in peptoids allow H-bonding, which is absent from the parent backbone, due to the unique indole ring. Furthermore, the rigid hydrophobic core and flat aromatic system influence the positioning in the hydrocarbon core and allows accommodating tryptophan-like side chains into the interfacial regions of bacterial membranes and causing bacterial membrane damage. Incorporating multiple tryptophan-like side chain in peptoids can be tricky and there is a lack of suitable, synthetic routes established. In this paper, we present guidelines for synthesis of peptoids rich in Nhtrp and Ntrp residues. We suggest resin, optimized cleavage conditions and choice of amine suitable for automated solid-phase sub-monomer peptoid synthesis route.